DIVERSITY OF NEPENTHES SPECIES IN NORTH SUMATRA PROVINCE - Mansur Halik; Andi Salamah; Edi Mirmanto (BERITA BIOLOGI, 2022)
Sumatra is the second island after Borneo, which has the highest diversity of Nepenthes species, spread from the lowlands to mountain forests. There are 38 species of Nepenthes recorded on Sumatra Island, and 33 of them are endemic. The study was conducted in 2019 and 2022 to know the diversity of Nepenthes in North Sumatra Province. The results showed that 22 species of Nepenthes were recorded in North Sumatra Province, consisting of 12 highland species, 3 midland species and 7 lowland species. N. tobaica is a highland species with a very wide distribution, spread over eight regencies in North Sumatra with a very abundant population, while N. sumatrana, N. rigidifolia, N. jamban, N. lingulata, and N. naga have limited distribution with a very small population and are potentially extinct.